Advanced students’ L1 (Swedish) and L2 (English) mastery of suffixation - Karlsson, Monica (International Journal of English Studies, 2015)
Developing the skill to form derivatives is a slow incremental process even for native speakers of English, starting in elementary school and continuing through high school. In fact, it appears to be a universally challenging area of the lexicon. Nevertheless, studies have shown that it is one of the most important skills to possess for a learner aiming to enlarge his/her L2 vocabulary and that it therefore may be worth the while for learners spending time on gaining mastery of derivative forms. In the present investigation, 15 Swedish first- term university students were asked to take two gap-filling context-based tests on suffixation, one in their L1 (Swedish) and one in their L2 (English), both of which were frequency-based (both stem and suffix considered). The students were also asked to evaluate their L1 and L2 knowledge of suffixation. The present study thus addresses the following research questions: Considering 1) the combined frequency of the stem and suffix, 2) the complexity of the suffix (in terms of frequency, predictability, productivity and regularity) and 3) what word classes the suffixes are able to form, what 1) quantitative and 2) qualitative knowledge of suffixation do Swedish university students have in English as their L2 as compared to their L1?